Numbers of genes in the NBS and RLK families vary by more than four-fold within a plant species and are regulated by multiple factors - Zhang, Meiping; Wu, Yen-Hsuan; Lee, Mi-Kyung; Liu, Yun-Hua; Rong, Ying; Santos, Teofila S.; Wu, Chengcang; Xie, Fangming; Nelson, Randall L.; Zhang, Hong-Bin (Elsevier, 2010)
Many genes exist in the form of families; however, little is known about their size variation, evolution and biology. Here, we present the size variation and evolution of the nucleotide-binding site (NBS)-encoding gene family and receptor-like kinase (RLK) gene family in Oryza, Glycine and Gossypium. The sizes of both families vary by numeral fold, not only among species, surprisingly, also within a species. The size variations of the gene families are shown to correlate with each other, indicating their interactions, and driven by natural selection, artificial selection and genome size variation, but likely not by polyploidization. The numbers of genes in the families in a polyploid species are similar to those of one of its diploid donors, suggesting that polyploidization plays little roles in the expansion of the gene families and that organisms tend not to maintain their 'surplus' genes in the course of evolution. Furthermore, it is found that the size variations of both gene families are associated with organisms' phylogeny, suggesting their roles in speciation and evolution. Since both selection and speciation act on organism's morphological, physiological and biological variation, our results indicate that the variation of gene family size provides a source of genetic variation and evolution.